Teknik Mimicry Memorization Dalam Pembelajaran Kosakata Bahasa Arab: Studi Kasus Pada Kelas 2 di Sebuah Sekolah Dasar Islam Tangerang Selatan - Veronica Rahmatin; Hotimin; Hari Febriansyah (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
This study aims to describe the application of the mimicry-memorization technique in teaching Arabic vocabulary to second-grade students at an Islamic Elementary School in South Tangerang. Arabic plays an essential role in islamic education, yet it is often perceived as difficult from Indonesian. Therefore, an appropriate teaching technique that aligns with young’s learning characteristics is needed to help them gradually master basic vocabulary. This research employed a qualitative approach with a case study design. Data were collected through unstructured interviews, participant observation, documentation, and analyzed using Miles and Huberman’s model, including data reduction, display, and conclusion drawing. The findings reveal that the teacher implemented the mimicry-memorization technique through four main stages: listening, imitating, repeating, and memorizing vocabulary. The teacher acted as a language model by providing clear pronounciation examples, while students preated the words collectively. This and reinforced their memory through repetition. However, the study also identified signs of boredom among students and difficulties in memorization when learning lacked engaging media. Therefore, the mimicry-memorization technique should be integrated with visual aids and games to better match the characteristics of elementary learners. When applied creatively, this technique can serve as a relevant and meaningful approach to arabic vocabulary learning in primary education.